Environmental, Social and Governance Responsibility, financial performance and assets: A study of Exchange Traded Funds - Rompotis, Gerasimos (Research Papers in Economics and Finance, 2023)
Two research questions are examined in this study with a sample of 168 passive Exchange Traded Funds (ETFs). The first one asks whether a high Environmental, Social and Governance Responsibility (ESG) rating induces investors to allocate more money in an ETF. The empirical findings indicate that the level of assets is not affected by the ESG rating whatsoever, but it is affected by factors such as the historical performance, the expense ratio and the age of each fund. The second question raised concerns the relationship between the performance of an ETF and its ESG rating. The hypothesis examined is that the higher the ESG rating of an ETF is, the higher the return of the ETF should be. The results do not confirm this hypothesis. Not surprisingly, to a large extent, the performance of ETFs is driven by the return of the tracking indexes. To a lesser degree, expense ratio bears a negative impact on ETFs’ performance.